2019
DOI: 10.3389/fpsyg.2019.00475
|View full text |Cite
|
Sign up to set email alerts
|

Variables Influencing Cryptocurrency Use: A Technology Acceptance Model in Spain

Abstract: The first commercial transaction with the first cryptocurrency in 2010 marked the start of a revolution in transactions. Blockchain and cryptocurrencies will dramatically transform how we do transactions, just as the Internet revolutionized how we communicate. Currently, more than 2,000 cryptocurrencies are quoted on the market, and many more are being launched in initial coin offerings for use as an exchange method in a specific business ecosystem or as rights to assets or liabilities. As an emerging fintech,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
156
2
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(226 citation statements)
references
References 50 publications
18
156
2
9
Order By: Relevance
“…If Q2 is greater than zero, the model has predictive relevance; if it is less than or equal to zero, it does not. But this is a rule-of-thumb that does not take into account the sampling distribution of Q2 (Shmueli et al, 2016; Arias-Oliva et al, 2019). As shown in Table 11, the R2 values were greater than 0.1 for all the variables except the cognitive image and the unique image.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…If Q2 is greater than zero, the model has predictive relevance; if it is less than or equal to zero, it does not. But this is a rule-of-thumb that does not take into account the sampling distribution of Q2 (Shmueli et al, 2016; Arias-Oliva et al, 2019). As shown in Table 11, the R2 values were greater than 0.1 for all the variables except the cognitive image and the unique image.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…This research has been made with the same sample of adults from Spain as Arias-Oliva et al [7]. Literature on the application of TAMs on this topic is not so widespread and, due to the reasons above, all very recent.…”
Section: Introductionmentioning
confidence: 99%
“…Literature on the application of TAMs on this topic is not so widespread and, due to the reasons above, all very recent. Let us point out apart from [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Despite all reviewed literature is based in the use of TAMs, the final configuration of hypothesis to test and the use/user of cryptos under consideration have different nuances.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained from decision tree revealed that performance expectancy and facilitating conditions are the most influential factors in terms of cryptocurrency ownership in general. Arias-Oliva et. al., (2019) suggest that "the product and service design for a new cryptocurrency (or the innovation efforts for current ones) should focus on performance as the most critical adoption factor."…”
Section: Discussionmentioning
confidence: 99%